Associations of blood pressure in the third trimester and risk of venous thromboembolism postpartum - Qian Li; Hongfei Wang; Huafang Wang; Jun Deng; Zhipeng Cheng; Fengjuan Fan; Wenyi Lin; Ruiqi Zhu; Shi Chen; Jinrong Guo; Yuxiong Weng; Liang V. Tang; et al. (MedComm, 2024)
Abstract Studies on the associations of blood pressure (BP) and the risk of venous thromboembolism (VTE) had been performed neither among pregnant women nor in Chinese population. This study included participants of pregnant women from a retrospective multicenter cohort, between May 2020 and April 2023. Systolic BP (SBP) and diastolic BP (DBP) of the participants were measured in the third trimester. The incidences of VTE (including deep venous thrombosis and/or pulmonary embolism) at 42 days postpartum were followed. With regards to SBP, pregnant women in the Q1 (≤114 mmHg), Q2 (115–122 mmHg), and Q4 group (≥131 mmHg) had increased risk of VTE than those in Q3 group (123–130 mmHg), with ORs 4.48 [1.69, 11.85], 3.52 [1.30, 9.59], and 3.17 [1.12, 8.99], respectively. Compared with pregnant women with the Q4 of DBP (≥85 mmHg), women of Q1 (≤71 mmHg) were found to have elevated risk of VTE (OR 2.73 [1.25, 5.96]). A one standard deviation decrease of DBP (9 mmHg) was related with 37% elevated risk of VTE (OR 1.37 [1.05, 1.79]). This study demonstrated a U‐shaped association of SBP in the third trimester and VTE postpartum and inverse association of DBP in the third trimester and VTE postpartum.